COMMUNITY POLICING IN BORDER COMMUNITIES - Boluža, Inese (Border Security and Management, 2016)
Community orientated policing is widely held as the relatively new and interesting philosophy for Latvian policing. For the fifteen years the community policing movement has been gaining momentum acquiring the support of politicians, reformers, and the society. Unfortunately there are problems that continually plague the philosophy of community policing. Some of the largest obstacles that police organizations face with the community policing program are the initial implementation and understanding of community policing, the ability to change and adapt to the new format of policing, and the acceptance.As part  reform programs, State police of Latvia seek to introduce community policing. There is no clear or consistent definition of what constitutes a community policing programme. However, most community policing initiatives aim to improve relations between the police and residents, engage community members or civic organizations in evaluation of police services, and expand information sharing. Community policing control activities are not always linked to police reform initiatives; somestimes the two activities occur simultaneously in isolation on each other. There have been more increasing attempts to link or find synergies between control initiatives and realised programs, especially (community-based) weapons collection programs and disarmament and demobilization projects. Policing reform has been a rather neglected area of security sector reform that has been addressed on an ad hoc basis. Some analysts see the need to reduce the number of firearms in circulation as a way to improve public security, and thus training in the management of safeguarding police stockpiles, keeping accurate inventories of weapons and appropriate weapons handling need to be reinforced.Public safety cannot be taken for granted. It can only be achieved not only through the professionalism of our finest, but through successful collaboration with their neighboring counterparts as well. They all deserve our respect and gratitude, and not calumny and frivolous criticisms.